Digital forensics research using constraint programming - a preliminary approach - Calhau, João (2022)
The world today is becoming more and more digital, as such there is a huge amount of data constantly being created, transmitted and saved every second. Representing this data in digital form, although it brings some advantages it also brings some disadvantages and challenges when we need to make an analysis of the content of said data. For this same reason, it was created the discipline of digital forensics, which focuses on the analysis of digital equipment content. This document introduces an approach on using constraint programming methods in digital forensics analysis, allowing for an easier and more efficient method to analyze digital equipment data.